Distributing Over Sets

True or false :

\quad There exist three nonempty sets A A , B B , and C C such that
\quad A ( B C ) ( A B ) ( A C ) A\cup (B-C)\neq (A\cup B)-(A\cup C) .

True False

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Shawn Franchi
Apr 29, 2016

Relevant wiki: Sets - Multiple sets

For example, let A = { a } B = { b } C = { c } A=\{ a\} \\ B=\{ b\} \\ C=\{ c\}

The union A ( B C ) A\cup(B-C) is the set { a , b } \{ a, b\} .

The set A B = { a , b } A\cup B=\{ a,b\} and the set A C = { a , c } A\cup C=\{ a,c\} .

So their set difference is { a , b } { a , c } = { b } \{ a,b\} -\{ a,c\} =\{ b\} , which is not equal to the set { a , b } \{ a, b\} .

In general, for cases where A A is nonempty, the union A ( B C ) A\cup(B-C) will be distinct from the set difference ( A B ) ( A C ) (A\cup B)-(A\cup C) because all members of set A A are in the former, and no elements of A A are in the latter.

Note: Here, the notation X Y X - Y refers to the relative complement of the set X X with the set Y Y , also notated as X Y X \setminus Y .

Moderator note:

Great explanation that A [ A B A C ] = A \cap [ A \cup B - A \cup C ] = \emptyset .

Is there a simple expansion for A ( B C ) A \cup (B-C) ?

nice but iam dont sea = ...... true

Patience Patience - 5 years, 1 month ago

Will Distributive Law apply here?

Jhann Soriano - 10 months, 3 weeks ago
Bethany Waanders
May 23, 2021

https://brilliant.org/discussions/thread/venn-diagrams-and-set-notation/ There exist three nonempty sets A, B, and C such that A∪(B−C) ≠(A∪B)−(A∪C). When {a,b,d,g,e} ≠ {b}
From the diagram and by definitions:

A={a,d,e,g}, B={b,d,f,g}, C={c,e,f,g}

(B−C)={b,d,f,g}-{c,e,f,g}={b,d}

(A∪B)={a,d,e,g}∪{b,d,f,g}={a,b,d,e,f,g}

(A∪C)={a,d,e,g}∪{c,e,f,g}={a,c,d,e,f,g}

A∪(B−C)= {a,d,g,e} ∪ {b,d}= {a,b,d,g,e}

(A∪B)−(A∪C) = {a,b,d,e,f,g}-{a,c,d,e,f,g}= {b}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...